2020
DOI: 10.1101/2020.03.11.20034546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental contamination of the SARS-CoV-2 in healthcare premises: An urgent call for protection for healthcare workers

Abstract: ImportanceA large number of healthcare workers (HCWs) were infected by SARS-CoV-2 during the ongoing outbreak of COVID-19 in Wuhan, China. Hospitals are significant epicenters for the human-to-human transmission of the SARS-CoV-2 for HCWs, patients, and visitors. No data has been reported on the details of hospital environmental contamination status in the epicenter of Wuhan. ObjectiveTo investigate the extent to which SARS-CoV-2 contaminates healthcare settings, including to identify function zones of the hos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 9 publications
1
46
0
2
Order By: Relevance
“…It also stays on rough surfaces such as fabric and wood for up to 2 days (Chin et al 2020). Another investigation, which examined environmental levels of SARS-CoV-2 virus in hospital centers, found that the most important environmental levels of infection were self-service printers (20%) (used in Chinese laboratories), desktops, and keyboards (16.8%), door handles (16%), telephones (12.5%), and medical equipment (12.5%) (Ye et al 2020). Studies show that students touch their face with their hands an average of 23 times an hour.…”
Section: Inanimate Surface and Disinfectionmentioning
confidence: 99%
“…It also stays on rough surfaces such as fabric and wood for up to 2 days (Chin et al 2020). Another investigation, which examined environmental levels of SARS-CoV-2 virus in hospital centers, found that the most important environmental levels of infection were self-service printers (20%) (used in Chinese laboratories), desktops, and keyboards (16.8%), door handles (16%), telephones (12.5%), and medical equipment (12.5%) (Ye et al 2020). Studies show that students touch their face with their hands an average of 23 times an hour.…”
Section: Inanimate Surface and Disinfectionmentioning
confidence: 99%
“…The second is through indirect contact with virus contaminated surfaces 6,7 , as following sneezing and coughing, the virus containing saliva droplets can spread 1-2 m and deposit on surfaces 8 . The virus can remain viable on surfaces between hours and days, depending on the inoculum shed and environmental conditions 9 .…”
Section: Main Textmentioning
confidence: 99%
“…A study by Ye et al (2020) on the contamination levels of healthcare settings found that the most contaminated objects were self-service printers, desktop/keyboards, doorknobs, and hand sanitiser dispensers, all of which can be found in medical photography departments.…”
Section: Virus Survival Rates On Photographic Equipmentmentioning
confidence: 99%